2023
DOI: 10.1073/pnas.2305772120
|View full text |Cite
|
Sign up to set email alerts
|

Ketamine and the neurobiology of depression: Toward next-generation rapid-acting antidepressant treatments

John H. Krystal,
Alfred P. Kaye,
Sarah Jefferson
et al.

Abstract: Ketamine has emerged as a transformative and mechanistically novel pharmacotherapy for depression. Its rapid onset of action, efficacy for treatment-resistant symptoms, and protection against relapse distinguish it from prior antidepressants. Its discovery emerged from a reconceptualization of the neurobiology of depression and, in turn, insights from the elaboration of its mechanisms of action inform studies of the pathophysiology of depression and related disorders. It has been 25 y since we first presented … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 218 publications
(252 reference statements)
0
4
0
Order By: Relevance
“…We screened four available antibodies, including Immunostar antibody specificity of which was confirmed in 5HT2a KO mice 2 . To examine the specificity of the antibodies we initially used CHO-K1 cells transiently transfected with mouse 5HT2a-IRES-GFP construct in which GFP expression should correspond to 5HT2a expression.…”
Section: Supplementary Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…We screened four available antibodies, including Immunostar antibody specificity of which was confirmed in 5HT2a KO mice 2 . To examine the specificity of the antibodies we initially used CHO-K1 cells transiently transfected with mouse 5HT2a-IRES-GFP construct in which GFP expression should correspond to 5HT2a expression.…”
Section: Supplementary Materialsmentioning
confidence: 99%
“…Neuroplasticity is a broad term capturing a wide range of processes in the nervous system that take place in response to the changing environment. Induction of certain forms of beneficial neuroplasticity has become a global neurobiological explanatory model of our times for the effects of neuro-therapeutics such as SSRI antidepressants and psychedelics 1,2 . Similarly, molecular targets associated with neuroplasticity have garnered attention as potential avenues for therapeutic intervention 3 .…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, even though traditional antidepressants are effective in most patients, their efficacy is limited by a delay of therapeutic onset of several weeks and by a high percentage of non-response and disease recurrence [ 172 ]. Preclinical studies have revealed that the rapid antidepressant effect of ketamine is associated with the restoration of dysfunctional glutamatergic transmission and promotion of neuroplasticity in corticolimbic areas [ 150 , 173 , 174 , 175 ].…”
Section: Glutamatergic Alterations In Major Depressive Disorder and P...mentioning
confidence: 99%
“…Ketamine-induced functional and structural plasticity has been extensively described in the postsynaptic context. For example, a prominent theory for the potentiation of glutamatergic signalling is that ketamine disinhibits glutamatergic neurons by preferentially blocking NMDARs on GABAergic neurons 3,4,6 . This is sometimes called the “presynaptic effect” but refers to increased neuronal activity of glutamatergic neurons rather than to direct effects of ketamine on presynaptic nerve terminals.…”
mentioning
confidence: 99%
“…Although the time scale of 30 min to one hour in our study is much shorter than the time scale of days for antidepressant effects of ketamine in patients, the here-observed enhanced presynaptic release demonstrates that ketamine induces a long-lasting presynaptic plasticity 14 . The increased glutamate release might contribute to the glutamate surge observed in patients, which is thought to induce neuronal-circuit potentiation that mediates the antidepressant effects of ketamine 46 . However, further studies are needed to investigate the direct link between presynaptic potentiation and antidepressant effects of ketamine.…”
mentioning
confidence: 99%